Provision of Road Infrastructure as An Effort to Guarantee Area Accessibility in Order to Encourage Trade and Services Activities in the Nagoya Trade and Services Area, Batam City - Suhar, Suhar; Sidabutar, Yuanita FD (Graduate Program Magister Manajemen Pendidikan, 2023)
This research is intended to analyze the influence of the quality of infrastructure services on the development of economic activities, especially trade and services activities in the Nagoya trade and services area, Batam City, using 6 indicators as a benchmark to evaluate the extent to which infrastructure development has an influence on the development of trade and services activities in the trade and services area. Nagoya, Batam City by testing the quality of available infrastructure services, including: (1). Physical availability, (2). Physical quality, (3). Suitability, (4). Effectiveness of utilization, (5). Absorption of labor and (6). Contribution to the economy. The Nagoya trade and services area is one of the first and largest trade and services areas in Batam City to date and is currently still a magnet for everyone to come to Batam City to visit this area. The Nagoya Trade and Services Area has 63 shopping complexes, 7 markets with permanent buildings, 55 mini markets, 1099 shops, 203 restaurants and 1111 food stalls, while in terms of services this area has 64 service institutions finance consisting of 18 government banks, 29 private banks and 17 people's credit banks and supported by accommodation facilities of 126 entities consisting of 106 hotels and 20 guesthouses.